Probiotics in Gut Health and Immunity: Mechanisms and Clinical Evidence - Filipski, Michał; Wróbel, Bartosz; Wójcik, Lena; Gadzalski, Krzysztof; Owczarenko, Konstancja; Szada-Borzyszkowski, Kacper (Journal of Education, Health and Sport, 2026)
Background. Probiotics are live microorganisms that support human health mainly by influencing the gut microbiota. They help maintain the integrity of the intestinal barrier and play an important role in regulating immune responses. Their growing clinical relevance is linked to conditions associated with microbiota imbalance. Aim. The aim of this review was to present the main mechanisms of probiotic action and to assess their clinical effectiveness in selected gastrointestinal, infectious, and allergic diseases. Material and methods. This narrative review is based on data from randomized controlled trials and meta-analyses focusing on both molecular mechanisms and clinical outcomes of probiotic use. Results. Probiotics improve intestinal barrier function by supporting tight junction proteins and reducing intestinal permeability. They also modulate immune responses by limiting inflammation and promoting regulatory pathways, including the induction of regulatory T cells. Clinical studies show that multistrain preparations, especially those containing Lactobacillus and Bifidobacterium, are effective in reducing the risk of antibiotic-associated diarrhea and Clostridioides difficile infection. They also help relieve symptoms of functional gastrointestinal disorders and improve outcomes in allergic diseases such as atopic dermatitis and childhood asthma. Overall, probiotics are well tolerated and safe. Conclusions. Probiotics can be a valuable supportive therapy in disorders related to microbiota imbalance. Further studies should focus on better matching specific strains to individual patients in order to increase treatment effectiveness.